Photodynamic therapy of lung cancer, where are we? - Crous, Anine; Abrahamse, Heidi (Frontiers in Pharmacology, 2022)
Lung cancer remains the leading threat of death globally, killing more people than colon, breast, and prostate cancers combined. Novel lung cancer treatments are being researched because of the ineffectiveness of conventional cancer treatments and the failure of remission. Photodynamic therapy (PDT), a cancer treatment method that is still underutilized, is a sophisticated cancer treatment that shows selective destruction of malignant cells via reactive oxygen species production. PDT has been extensively studied in vitro and clinically. Various PDT strategies have been shown to be effective in the treatment of lung cancer. PDT has been shown in clinical trials to considerably enhance the quality of life and survival in individuals with incurable malignancies. Furthermore, PDT, in conjunction with the use of nanoparticles, is currently being researched for use as an effective cancer treatment, with promising results. PDT and the new avenue of nanoPDT, which are novel treatment options for lung cancer with such promising results, should be tested in clinical trials to determine their efficacy and side effects. In this review, we examine the status and future potentials of nanoPDT in lung cancer treatment.